Hybrid Maize and Chilli Intercropping in the Hilly Areas of Bandarban (Bangladesh Agronomy Journal, 2016)
The experiment was conducted at farmers field of On-Farm Research Division (OFRD), Bandarban during Rabi season of 2014-15 to find out suitable combination of hybrid maize and chilli intercropping system to increase system productivity and economic return. The experimental design was Randomized Complete Block (RCB) design with six dispersed replications. The maize var. BARI Hybrid Maize-9 and chilli (local) were used in the experiment. Two intercropping combinations viz., Maize single row (100 cm x 25 cm) + 2 rows chilli (50 cm x 40 cm) and Maize single row (150 cm x 25 cm) + 3 rows Chilli (50 cm x 40 cm) were evaluated against their sole crops. The highest gross return (Tk. 435040 ha-1), net return (Tk. 366290 ha-1) and benefit cost ratio (6.33) were recorded in maize single row (150 cm x 25cm) + 3 rows Chilli (50 cm x 40 cm) combination. Cob yield of hybrid maize and green fruit yield of Chilli were the highest in the respective sole crops. The results revealed that maize single row (150 cm x 25 cm) + 3 rows Chilli (50 cm x 40 cm) combination might be suitable and economically profitable for the hilly areas.Bangladesh Agron. J. 2016, 19(1): 45-48